1989
DOI: 10.1159/000276037
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Lymphoblastoid Transformation of Cells Obtained from Human Tonsils

Abstract: Spontaneous lymphoblastoid transformation of cells obtained from 25 human tonsils were investigated. Three Epstein-Barr virus (EBV) genome-positive lymphoblastoid cell lines were spontaneously established in tissue cultures in vitro from human tonsils. In addition, the frequency of spontaneous lymphoblastoid transformation was increased by the treatment of tumor promoter, 12-0-tetradecanoylphorbol-13-acetate and 18 lymphoblastoid cell lines were established. The data suggest that the human tonsil is a reservoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A previous study demonstrated that EBV-infected sLCLs were obtained from tonsillar tissues by bulk cultivation of minced tonsillar tissues in medium supplemented with 12- o -tetradecanoylphorbol 13-acetate (TPA) [16]. We applied the protocol to tonsillar tissues obtained from 17 patients undergoing routine tonsillectomies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study demonstrated that EBV-infected sLCLs were obtained from tonsillar tissues by bulk cultivation of minced tonsillar tissues in medium supplemented with 12- o -tetradecanoylphorbol 13-acetate (TPA) [16]. We applied the protocol to tonsillar tissues obtained from 17 patients undergoing routine tonsillectomies.…”
Section: Resultsmentioning
confidence: 99%
“…Tonsil-derived sLCLs were established according to a previous study [16]. Briefly, tonsillar tissues were minced, and red blood cells were removed by ACK lysis buffer (0.15 M NH 4 Cl, 10 mM KHCO 3 and 1 mM EDTA-2Na) treatment.…”
Section: Establishment Of Ebv-immortalized B-cell Lines From Tonsilla...mentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally arising LCLs are available from various sources. For example, they can be established from peripheral blood [ 42 ] or from tonsillar tissues obtained by routine tonsillectomy [ 43 ]. These naturally arising LCLs can serve as ideal resources to investigate EBV strain variation among individuals.…”
Section: Applications Of Crispr/cas9-mediated Cloning Of Ebvmentioning
confidence: 99%
“…However, spontaneous cellular immortalization has been observed in human somatic cells from patients with genetic disorders [1][2][3][4]. The transformation efficiency of spontaneous lymphoblastoid cell lines (SP-LCLs) was increased by tumor promoter treatment [8], radiation [9], and sometimes in cyclosporine-containing medium from EBV-seropositive patients [10]. The transformation efficiency of spontaneous lymphoblastoid cell lines (SP-LCLs) was increased by tumor promoter treatment [8], radiation [9], and sometimes in cyclosporine-containing medium from EBV-seropositive patients [10].…”
Section: What Are Lcls?mentioning
confidence: 99%